Engineering education and practice : embracing a Catholic vision - Hallinan, K. P.; Heft, James (Notre Dame studies in ethics and culture, 2011)
Engineering Education and Practice: Embracing a Catholic Vision is a collection of essays exploring how major themes of Catholic social teaching--respect for the environment, sustainability, technological design, and service to the poor--all positively affect engineering curricula, students, and faculty. Many engineering programs at American universities focus solely on developing technological sophistication without promoting ethical and humanitarian priorities. The contributors to this collection argue, however, that undergraduate engineering education needs to be broadened beyond its current narrow restrictions. The authors of this unique collection, nearly all of whom are engineers themselves, show how some Christian universities in the United States have found creative ways of opening up their engineering curricula. They demonstrate how the professional education of engineers can be enriched not only by ethical and religious themes, which are typically isolated in humanities curricula, but also by special fieldwork courses that offer hands-on service-learning opportunities and embody a rich educational synthesis.